Metal-free oxidative hydrophosphinylation of 1, 7-enynes. Issue 3 (2nd February 2016) - Zhu, Yi-Long; Wang, De-Cai; Jiang, Bo; Hao, Wen-Juan; Wei, Ping; Wang, Ai-Fang; Qiu, Jiang-Kai; Tu, Shu-Jiang
Abstract : A new metal-free oxidative hydrophosphinylation of 1, 7-enynes for forming polyfunctionalized 3, 4-dihydroquinolin-2(1 H )-ones has been realized using readily accessible diarylphosphine oxide and TBPB as an oxidant. Abstract : A new metal-free oxidative hydrophosphinylation of 1, 7-enynes for forming polyfunctionalized 3, 4-dihydroquinolin-2(1 H )-ones has been realized using readily accessible diarylphosphine oxide and TBPB as an oxidant. The reaction pathway involves an in situ -generated P-centered radical-triggered α, β-conjugate addition/6- exo -dig cyclization/H-abstraction sequence, providing a direct and promising protocol for the formation of C–P, C–C and C–H bonds and rapid construction of complex heterocyclic compounds.